PENGARUH FAKTOR-FAKTOR PRODUKSI TERHADAP PEMBAPATAN BAWANG MERAH DIDESA LAPANDEWA KAINDEA KECAMATAN LAPANDEWA KABUPATEN BUTON SELATAN - Mustari, La Ode Muhammad (Media Agribisnis, 2017)
Abstract   The problem statement in this research is: Whether the factors of production (land area and seeds) affect the income of shallot farming in Lapandewa Kaindea, Lapandewa sub-district, South Buton Regency? The purpose of this study was to determine whether the factors of production (Land area and seeds) affect the income of onion farming in Lapandewa Kaindea Village, Lapandewa Sub-district, South Buton Regency. The Population of this study is the onion farmers in Lapandewa Kaindea Village, Lapandewa sub-district, South Buton Regency. The researcher?s sample took was 32 farmers. Data were collected through interviews using questionnaires and analyzed using income analysis. Based on the results of the study, it was concluded that farmers in Lapandewa Kaindea Village, Lapandewa District, South Buton Regency, were the factors of production in the form of costs (labor, seeds, and fertilizer) that significantly affected the red onion farming income. With an R2 value of 0.981. This means that the factors of production in the form of (labor, seeds, and fertilizer) have an effect of 98.10% only, the rest is influenced by other factors not discussed in this study. Recommendations on the part of the government are expected to give more attention to farmers, both in the form of handling fertilizer prices, fertilizer, and fake fertilizer distribution.   Keywords: Effect of production factors, revenue, onion